Evicting Palestine. (1st April 2016) - Penny Green; Amelia Smith
Abstract : Israel is engaged in a systematic and illegal scheme of forced evictions against Palestinians. Forced evictions of Palestinians, and the human rights abuses they suffer as a result, are known, and yet largely ignored by the international community. In this article, Penny Green and Amelia Smith expose this crime by documenting the key methods adopted by the Israeli state to achieve the goal of "Evicting Palestine" – village and house demolitions, unrecognizing Bedouin villages, the separation wall, settlement expansion and historical claims to the land. The article is based primarily on extensive fieldwork that the authors carried out in March 2014. The article reveals that these various methods of forced displacement contribute to an over-arching and ongoing process, the primary aim of which is to construct new spaces that exclude Palestinians from their ancestral land in order to expand the Israeli-Jewish population and to increase colonial control and annexation of Palestinian territory.